2018
DOI: 10.24815/jn.v18i2.11163
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Natural Iron Sand From Kata Beach, West Sumatra With High Energy Milling (Hem)

Abstract: Iron sand is one of the natural resources in West Sumatra that has not been optimally utilized. One of the potential locations to get this iron sand deposits is the coast of Kata. This study aims to analyze the content and size of the iron grains found on the coast of Kata Padang Beach, West Sumatera Province. Coastal sand samples are extracted using permanent magnets to separate magnetic and non-magnetic materials. Characterization of iron sand using Scanning Electron Microscopy with Energy Dispersive X-ray (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 7 publications
2
12
0
5
Order By: Relevance
“…The XRD results of this study are in agreement with the findings of Rianna et al. [ 33 ], who characterised sea sand on the west coast of Sumatra. Elements such as C, O, Al, Si, Ca, Mn, and Fe were the dominant elements found in sea sand.…”
Section: Resultssupporting
confidence: 93%
“…The XRD results of this study are in agreement with the findings of Rianna et al. [ 33 ], who characterised sea sand on the west coast of Sumatra. Elements such as C, O, Al, Si, Ca, Mn, and Fe were the dominant elements found in sea sand.…”
Section: Resultssupporting
confidence: 93%
“…Another study confirmed that the iron sand deposit in Java was derived from denudation of andesite and old andesite formation enriched in magnetite and ilmenite minerals [9]. Several studies of iron sand from Sumatera revealed the magnetite minerals were also dominant, hence lower magnetic properties [10,11].…”
Section: Introductionmentioning
confidence: 91%
“…Endapan pasir besi di Indonesia telah dikenal menyebar di sepanjang pesisir Sumatra, Jawa, Pulau Sunda Kecil, Sulawesi dan Nusa Tenggara Barat (Nugraha et al, 2016) dan kepulauan Maluku (Fakhrurrozi, 2015). Pasir besi yang berasal dari pantai maupun sungai ini, memiliki kandungan besi seperti besi oksida hematite (Fe2O3) dan magnetite (Fe3O4) serta senyawa yang lain seperti Fe, Zn, dan Ni (Fitria & Ramli, 2017), titanium (Rianna et al, 2018). Kandungan yang banyak pada pasir besi ini dapat digunakan di bidang perindustrian seperti sebagai bahan campuran untuk membuat semen agar memiliki kualitas yang baik, serta digunakan dalam pembuatan tinta serta berpotensi sebagai bahan magnet dalam pembuatan keramik (Togibasa, 2019).…”
Section: Pendahuluanunclassified